Detection and Characterization of ESBL-Producing Escherichia coli From Humans and Poultry in Ghana - Falgenhauer, Linda; Imirzalioglu, Can; Oppong, Kwabena; Akenten, Charity Wiafe; Hogan, Benedikt; Krumkamp, Ralf; Poppert, Sven; Levermann, Vinzent; Schwengers, Oliver; Sarpong, Nimako; Owusu-Dabo, Ellis; May, Jürgen; et al. (Frontiers in Microbiology, 2019)
Introduction: The increasing incidence of infections caused by Extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli in sub-Saharan Africa is of serious concern. Studies from countries with a highly industrialized poultry industry suggest the poultry production-food-consumer chain as a potential transmission route. In Africa, integrated studies at this human-animal interface are still missing. Aim: To determine the molecular epidemiology of ESBL-producing E.coli from the intestinal tract of humans and poultry in rural Ghana. Methods: During a six-month period, fecal samples from all children admitted to the Agogo hospital (Ghana) and broilers at eight poultry farms located within the hospital catchment area were collected. After screening on selective ESBL agar, Whole Genome Sequencing (WGS) was performed on all ESBL isolates. The genomes were analysed using Multilocus Sequence Typing (MLST), ESBL genotyping and genome-based phylogenetic analyses. Results: Of 140 broilers and 54 children, 41 (29%) and 33 (61%) harbored ESBL E.coli, respectively, with prevalences on farms ranging between 0% and 85%. No predominant sequence type (ST) was detected among humans. ST10 was most prevalent among broilers (n=31, 69%). The ESBL gene blaCTX-M-15 was predominant among broilers (n=43, 96%) and humans (n=32, 97%). Whole-genome-based phylogenetic analysis revealed three very closely related broiler/human isolate clusters (10% of ESBL isolates) with chromosomal and plasmid-mediated ESBL genes. Conclusion: The findings demonstrate a high frequency of intestinal ESBL-producing E.coli in rural Ghana. Considering that animal and human samples are independent specimens from the same geographic location, the number of closely related ESBL isolates circulating across these two reservoirs is substantial. Hence, poultry farms or meat products might be an important source for ESBL-producing bacteria in rural Ghana leading to difficult-to-treat infections in humans.